Biogenic proxies, dust particles, teleconnections, carbon export and sub-orbital scalesfrom the composite sediment core MV99 GC41/PC14 - Elsa Arellano-Torres; Catalina Álvarez-Covelli; Juan José Kasper-Zubillaga; María del Socorro Lozano-García (PANGAEA, 2018)
To study shifts in phytoplankton proxies linked to terrigenous inputs and teleconnections, we analyze the composite core MV99 GC41/PC14 from Soledad Basin, Gulf of Ulloa, NW Mexico. We used biogenic opal (% opal), organic carbon (% TOC) and inorganic carbon (% CaCO3) as proxies of productivity; and opal/TOC and CaCO3/TOC ratios as proxies of nutrient uptake and C-export by siliceous and carbonate organisms. We reconstructed terrestrial inputs using grain size Weibull analyses. Grain size analyses show significant amounts of fine fraction (between 0.06 - 6.6 μm) present during the early- to mid-Holocene in agreement to extreme weather on land, with episodes of aeolian and fluvial transport to the sea. The found that ENSO-like variations influence biological C-export producers on a scale of 1.1-1.8 ka, although PDO-related variability is uncertain. We suggest that Holocene drivers for phytoplankton successions are changes in insolation, ITCZ migration, California Current upwelling, nutrient inputs by advection and terrestrial sources.
Supplement to: Arellano-Torres, E et al. (2019): A 14-ka Record of Dust Input and Phytoplankton Regime Changes in the Subtropical NE Pacific: Oceanic and Terrestrial Processes Linked by Teleconnections at Suborbital Scales. Paleoceanography and Paleoclimatology, 34(1), 35-53, https://doi.org/10.1029/2018PA003479